Incidencia de la contaminación orgánica y de metales pesados sobre la biodiversidad marino costera del sitio Costa Rica - Espinoza Ruíz, Carlos Luis (2014)
Our coastal profile is one of the most polluted nationwide and generated many contaminants without any control, are discharged into canals that go directly into the sea, causing a high rate of contamination, so it is necessary the formulation of the following objectives: To determine the concentration levels of heavy metals in water, sediment and shells site Costa Rica, in the Archipelago Jambelí province of El Oro Compare and analyze results with the maximum permissible limits for preservation of flora and fauna. Among the conclusions developed in this investigation is determined that the value of heavy metals (arsenic, mercury, lead and cadmium) in the water sample, with indications were mercury contamination at the site Costa Rica, and significantly exceeding the maximum permissible limits. Parallel the results of the assessment of heavy metals (arsenic, mercury, lead and cadmium) in soil sample site Costa Rica, showed us that there is also mercury contamination at points C1, C2 and C3, and significantly exceeding maximum permissible limits. Finally, once tested for heavy metals (arsenic, mercury, lead and cadmium) in the sample of molluscs at the site Costa Rica, it was determined that contamination exists at all sampling points, because it significantly exceeded the maximum permissible limits.